The transformation of “the ethnic” in a tourist product in the province of Chaco, Argentina - Fernández, Patricia Torres (2010)
A few years ago, the province of Chaco initiated a process of “revaluation” of its “internal cultures” for bet to a national tourism that began to demand increasingly specialized destinies. In this process, it threw hand of all those “cultural elements” that, if they were not already transformed into tourist attraction, could turn in such. In this writing, I will focalize in the process that transforms “the ethnic” into tourist product through two mechanisms: re-categorizing the indigenous crafts as “located heritage” and revaluing the indigenous peoples as “cultural living heritage”. In this climate of patrimonial inflation, “the ethnic” trasforms in one more tourist product of the provincial offer. I will analyze the “ethnic tourism “ as practice-sense which cooperates to the conformation of a social field in which “ the ethnic” operates as device that includes, limits and simultaneously excludes “ multiple forms of the different”.